Reactive agility performance in handball; Development and evaluation of a sport-specific measurement protocol - Spasic, M.; Krolo, A.; Zenic, N.; Delextrat, A.; Sekulic, D. (Journal of Sports Science & Medicine, 2015)
There is no current study that examined sport-specific tests of reactive-agility and change-of-direction-speed (CODS) to repli-cate real-sport environment in handball (team-handball). This investigation evaluated the reliability and validity of two novel tests designed to assess reactive-agility and CODS of handball players. Participants were female (25.14 ± 3.71 years of age; 1.77 ± 0.09 m and 74.1 ± 6.1 kg) and male handball players (26.9 ± 4.1 years of age; 1.90 ± 0.09 m and 93.90±4.6 kg). Variables included body height, body mass, body mass index, broad jump, 5-m sprint, CODS and reactive-agility tests. Results showed satisfactory reliability for reactive-agility-test and CODS-test (ICC of 0.85-0.93, and CV of 2.4-4.8%). The reac-tive-agility and CODS shared less than 20% of the common variance. The calculated index of perceptual and reactive capaci-ty (P&RC; ratio between reactive-agility- and CODS-performance) is found to be valid measure in defining true-game reactive-agility performance in handball in both genders. There-fore, the handball athletes` P&RC should be used in the evalua-tion of real-game reactive-agility performance. Future studies should explore other sport-specific reactive-agility tests and factors associated to such performance in sports involving agile maneuvers.